2005
DOI: 10.1523/jneurosci.4173-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid Access to the GABAAReceptor

Abstract: GABA A receptors are a pivotal inhibitory influence in the nervous system, and modulators of the GABA A receptor are important anesthetics, sedatives, anticonvulsants, and anxiolytics. Current views of receptor modulation suggest that many exogenous drugs access and bind to an extracellular receptor domain. Using novel synthetic steroid analogs, we examined the access route for neuroactive steroids, potent GABA A receptor modulators also produced endogenously. Tight-seal recordings, in which direct aqueous dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
182
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(202 citation statements)
references
References 31 publications
16
182
2
2
Order By: Relevance
“…These results are complemented by results in which we found that potentiation of inside-out patches is robust when steroid is applied directly to the inner membrane leaflet (Fig. 3G), and we have synthesized a membrane-impermeant steroid with an ionically charged Alexa group substitution at C17 that only works from the inside of the membrane (Akk et al, 2005).…”
Section: A Access To Sitessupporting
confidence: 63%
See 3 more Smart Citations
“…These results are complemented by results in which we found that potentiation of inside-out patches is robust when steroid is applied directly to the inner membrane leaflet (Fig. 3G), and we have synthesized a membrane-impermeant steroid with an ionically charged Alexa group substitution at C17 that only works from the inside of the membrane (Akk et al, 2005).…”
Section: A Access To Sitessupporting
confidence: 63%
“…4 and Akk et al, 2005). We synthesized a fluorescent analogue of 3α5αP that retained activity at GABA A receptors and found that it accumulated in lipophilic regions of the cell, including plasma membrane and lipophilic intracellular compartments (Akk et al, 2005). These imaging results complement the cell-attached patch recording results and suggest the plausibility of membrane and/or intracellular access to steroid receptor sites.…”
Section: A Access To Sitesmentioning
confidence: 52%
See 2 more Smart Citations
“…The data also suggest that allopregnanolone synthesized in GABA-ergic neurons will be able to act at GABA A receptors postsynaptically or extrasynaptically (Belelli and Lambert, 2005). In glutamatergic neurons that express both 5α reductase and 3α HSD and that presumably synthesize allopregnanolone, the data suggest that allopregnanolone probably works in a paracrine fashion at GABA A receptors located on dendrites or cell bodies of those glutamatergic neurons, with or without secretion into the extracellular space, through plasma membrane lateral diffusion or through intracellular routes (Akk et al, 2005). Neurosteroid modulation of GABA-mediated currents involves G-protein and protein kinase activation Fancsik et al, 2000;Harney et al, 2003;Hodge et al, 2002;Vicini et al, 2002;Wegner et al, 2006).…”
Section: General Overviewmentioning
confidence: 83%